2020
DOI: 10.1111/eci.13386
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐to‐lymphocyte ratio and prognosis in STEMI: A meta‐analysis

Abstract: Background Platelet‐to‐lymphocyte ratio (PLR) is a haematological index which reflects increased level of inflammation and thrombosis. We aimed to summarize the potential prognostic role of PLR for the in‐hospital and long‐term outcomes in ST‐segment elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (pPCI) in a meta‐analysis. Materials and methods Relevant cohort studies were identified by search the PubMed, Cochrane's Library and Embase databases. A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 49 publications
0
41
0
6
Order By: Relevance
“…However, there is growing evidence for the role of inflammation in development and persistence of atrial fibrillation [ 47 ]. In a meta-analysis performed by Dong et al in STEMI patients, it was observed that a high PLR predicts poor in-hospital and long-term prognosis in patients undergoing PCI [ 48 ]. Several retrospective and prospective studies in patients with STEMI found that a high PLR was a predictor of no-reflow phenomenon in patients undergoing PCI [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing evidence for the role of inflammation in development and persistence of atrial fibrillation [ 47 ]. In a meta-analysis performed by Dong et al in STEMI patients, it was observed that a high PLR predicts poor in-hospital and long-term prognosis in patients undergoing PCI [ 48 ]. Several retrospective and prospective studies in patients with STEMI found that a high PLR was a predictor of no-reflow phenomenon in patients undergoing PCI [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been studied in several chronic inflammatory diseases and had a significant predictor of outcomes. [15][16][17][18] There is an increasing evidence that simple inflammatory biomarkers as P/LR as well as neutrophil to lymphocyte ratio (N/LR) can act as reliable predictors of a variety of medical conditions such as brain infarct, cerebral hemorrhage, and acute coronary syndrome [19][20][21]. The higher preprocedural P/LR predicts the shortand long-term prognosis after percutaneous revascularization interventions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Given the established relationship between IPF condition and some inflammation biomarkers [ 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ], we sought to determine the prognostic capacity of the combined blood cell count indexes, a group of well-recognized biomarkers of inflammation obtained by the complete blood cell count test, that is routinely provided in clinical practice. Ratios of blood cell counts have shown to be effective in predicting the survival of those with acute and chronic diseases [ 29 , 30 , 31 , 32 , 33 , 34 ]. Similar properties have also been exhibited by some blood cell dimensional indexes, such as the red blood cell distribution width (RDW), which has been reported to be an indicator of poor prognosis in IPF [ 10 , 35 ].…”
Section: Discussionmentioning
confidence: 99%